The Effectiveness of Digitizing Transaction Documents in Supporting Petty Cash Vouching Procedures - Trias Rachma Putri; Sri Trisnaningsih (International Journal of Economics, Management and Accounting, 2025)
Digitalization of transaction documents is a process of transferring transaction document media using a scanner. Digitalization of transaction documents is one of the supports for the efficiency of petty cash vouching procedures that have been implemented from 2025. The purpose of this research is to evaluate that implementation of transaction document digitization and assess the extent to which digitization is able to support the effectiveness of the petty cash vouching process. This research uses a descriptive qualitative method to obtain in-depth information about how the implementation of the digitization of petty cash transaction evidence. Interviews were conducted with 3 FAT (Finance, Accounting, Tax) staff. human resources, funds, machine tools, work methods, and document conditions are factors that support the implementation of digitization of transaction documents. In addition, in its implementation, there are still some obstacles that occur such as the absence of fixed procedures in digitizing proof of transactions, lack of human resources for the implementation of digitizing transaction documents, dependence on scanner devices, and systems that have not been integrated.